First record of Peridroma saucia Hübner (Lepidoptera: Noctuidae) in transgenic soybeans - Tamara A. Takahashi; Guilherme Nishimura; Eduardo Carneiro; Luís A. Foerster (Revista Brasileira de Entomologia, 2019)
The widespread cultivation of transgenic soybeans has caused significant changes in the spectrum of Lepidoptera larvae, both in the number of species as well as on their densities in the field. Transgenic crops producing Bacillus thuringiensis (Bt) insecticidal proteins have successfully reduced the incidence of the most common caterpillars infesting soybeans, namely Anticarsia gemmatalis (Lepidoptera: Erebidae) and Chrysodeixis includens (Lepidoptera: Noctuidae). However, lepidopteran species not previously recorded on the crop have been recently found, and are of concern due to the possibility of adaptation to the genetically modified cultivars. The occurrence of Peridroma saucia Hübner (Lepidoptera: Noctuidae) is described for the first time in Brazil feeding on genetically modified soybean cultivars. Keywords: Variegated cutworm, Bt soybean, Glyphosate tolerant soybean